2005
DOI: 10.1002/rcm.2144
|View full text |Cite
|
Sign up to set email alerts
|

Tandem mass spectrometry with online high‐flow reversed‐phase extraction and normal‐phase chromatography on silica columns with aqueous‐organic mobile phase for quantitation of polar compounds in biological fluids

Abstract: In this work, high-flow online reversed-phase extraction was coupled with normal phase on silica columns with aqueous-organic mobile phase liquid chromatography/tandem mass spectrometry (LC/MS/MS) to quantify drug candidates in biological fluids. The orthogonal separation effect obtained from this configuration considerably reduced matrix effects and increased sensitivity for highly polar compounds as detected by selected reaction monitoring. This approach also significantly improved the robustness and limit o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The results demonstrated that a reduction in ME was obtained when sufficient orthogonality of the phase systems was achieved. High-flow on-line reverse-phase extraction was coupled with normal phase on silica columns with aqueous-organic mobilephase LC-ESI-MSMS to quantify drug candidates in biological fluids (Deng et al, 2005). The orthogonal separation effect obtained from this configuration considerably reduced ME and increased sensitivity for highly polar compounds.…”
Section: B Chromatographymentioning
confidence: 99%
“…The results demonstrated that a reduction in ME was obtained when sufficient orthogonality of the phase systems was achieved. High-flow on-line reverse-phase extraction was coupled with normal phase on silica columns with aqueous-organic mobilephase LC-ESI-MSMS to quantify drug candidates in biological fluids (Deng et al, 2005). The orthogonal separation effect obtained from this configuration considerably reduced ME and increased sensitivity for highly polar compounds.…”
Section: B Chromatographymentioning
confidence: 99%
“…Coupling of reversed phase and HILIC has been successfully used to reduce matrix effects and increase sensitivity for highly polar compounds ( 20,21 ). A 2D-LC method was developed to separate HP-␤ -CD from the endogenous matrix using two orthogonal chromatographic separation mechanisms.…”
Section: Accuracy and Precisionmentioning
confidence: 99%
“…Highly aqueous mobile phases used for conventional online extraction conditions may cause peak distortion and " breakthrough " on HILIC analytical columns because water is a stronger solvent on HILIC. A gradient elution starting from high organic content (e.g., 90% acetonitrile in water) can provide better peak shape and retention (Deng et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%